Macroinvertebrados bentônicos como indicadores de qualidade da água em rios e reservatórios da bacia hidrográfica do Tietê-Jacaré (SP) - Pareschi, Daniela Cambeses (Universidade Federal de São Carlos, 2008)
The community of benthic macroinvertebrates from 21 pre-selected sample points, including rivers and reservoirs at the Tiete-Jacaré (SP) watershed, were sampled during periods of drought (jun/05) and rain (feb/08), using artificial substrates filled with expanded clay (1 month of colonization), as well as samples of natural substrate with Ekman-Birge dredger and core. The objective of this study was to analyze the richness and abundance of benthic macroinvertebrates (identified until the level of family, except for Chironomidae, which was identified until the level of gender) and it s relation to water quality, under two methods of sampling, artificial substrates and natural substrates, comparing also lotic and lentic systems. Several metrics were applied, such as BMWP (Biological Monitoring Working Party) and adaptations, the IBB (Belgian Biotic Index),% EPT and Shannon-Wiener diversity index, in order to verify it s relationship to water quality, analyzing physical, chemical and biological parameters of water and sediment. The artificial substrates were efficient in the colonization of the benthic macroinvertebrate both in rivers and reservoirs, providing greater richness and abundance than the samples with dredge or core. Most of the families collected with dredge or core were represented by Oligochaeta, Chironomidae and Mollusca, while in artificial substrates, a greater variety of orders of insects, crustaceans and other organisms were found. Greater richness and diversity of benthic macroinvertebrates, including groups that are sensitive to pollution as Ephemeroptera and Trichoptera, were found in more preserved places, with the presence of riparian vegetation and good water quality (low values of electrical conductivity, total phosphorus and fecal coliform). In places affected by sewage pollution, the greater abundance and dominance was found, especially from organisms that are tolerant to organic pollution, such as Oligochaeta, Chironomidae and Hirudinea. The genera of the family Chironomidae, Tanytarsus and Rheotanytarsus, were associated with better water quality, while the gender Chironomus gr. decorus occurred in great abundance in places impacted by domestic sewage. The application of biotic indices of water quality, BMWP and IBB, was satisfactory for both rivers and to the margins of reservoirs, although in the rainy season the results were not satisfactory, because of the loss of organisms.
Keywords: Macroinvertebrados bentônicos; Bioindicadores; Água - qualidade; Biomonitoramento; Limnologia, Água - poluição; CIENCIAS BIOLOGICAS::ECOLOGIA